The great cities in history - Norwich, John Julius, 1929-2018 (Thames and Hudson, 2009)
From the origins of urbanization in Mesopotamia to the global metropolises of today, great cities have marked the development of human civilization. The Great Cities in History tells their stories, from Uruk and Memphis to Tokyo and São Paulo. A galaxy of distinguished contributors evoke the character of each place its people, its art and architecture, its government and explain the reasons for its success. Richly illustrated with photographs, paintings, maps and plans, this volume is nothing less that a portrait of world civilization.